Inactivation of the E-Cadherin-Mediated Cell Adhesion System in Human Cancers - Hirohashi, Setsuo (American Society for Investigative Pathology, 1998)
It has long been known that cell-cell adhesiveness is generally reduced in human cancers. Tumor cells are dissociated throughout the entire tumor masses of diffuse-type cancers, whereas those of solid tumors with high metastatic potentials are often focally dissociated or dedifferentiated at the invading fronts. Thus, both irreversible and reversible mechanisms for inactivating the cell adhesion system appear to exist. This paper focuses on the cadherin system, which mediates Ca(2+)-dependent homophilic cell-cell adhesion. The E (epithelial)-cadherin-mediated cell adhesion system in cancer cells is inactivated by multiple mechanisms corresponding to the pathological features described above. Mutations have been found in the genes for E-cadherin and its undercoat proteins, α- and β-catenins, which connect cadherins to actin filaments and establish firm cell-cell adhesion. Transcriptional inactivation of E-cadherin expression was shown to occur frequently in tumor progression. E-cadherin expression in human cancer cells is regulated by CpG methylation around the promoter region. The cadherin system interacts directly with products of oncogenes, eg, c-erbB-2 protein and the epidermal growth factor receptor, and of the tumor suppressor gene, adenomatous polyposis coli (APC) protein, through β-catenin, which may be important in signal transduction pathways contributing to the determination of the biological properties of human cancers. In conclusion, inactivation of the E-cadherin system by multiple mechanisms, including both genetic and epigenetic events, plays a significant role in multistage carcinogenesis.